(untitled) (Physical Education, Health and Social Sciences, 2026)
This study investigates the ecolinguistic dimensions of Shakespeare’s The Tempest. A qualitative method was used to examine the play’s language, characters, and representation of the natural world. The analysis shows that language in the play is closely connected with social power relations and is used to shape order and authority. The findings further suggest that The Tempest contains clear ecological concerns and environmental imagery, reflecting Shakespeare’s appreciation of nature and his emphasis on the protection and value of natural elements.